ENDOCRINE DISRUPTORS AND THYROID HOMEOSTASIS IN ADULT BUFFALO - KAUR, KARANPREET; GHUMAN, S P S; BEDI, J S; GILL, J P S (The Indian Journal of Animal Reproduction, 2016)
The present study conducted on 80 adult buffalo screened their plasma samples for thyroid hormone profile andpesticide residues (endocrine disruptors). About 51 buffalo were pesticide negative and remaining had low (27.1±12.1ng/ml) or high (106.6±82.2 ng/ml) pesticide residues. However, circulating pesticides had no consistent (p>0.05)relation with plasma thyroid hormones
Keywords: Buffalo,; Endocrine Disruptor; Fertility,; Pesticide; Thyroid